Productivity of fourfinger threadfin (Eleutheronema tertadactylum) capture fishery in Bungur Village Rangsang Pesisir Sub-District Meranti Islands District, Riau Province - Mariono Situngkir; Alit Hindri Yani; Jonny Zain (South East Asian Marine Sciences Journal, 2023)
This study aimed to determine the productivity value of turtle catching in Bungur Village, Rangsang Pesisir District, Meranti District, Riau Province. The production of kurau nets for five years shows that fourfinger threadfin fishing effort and production fluctuate yearly. In the period from 2017-2021, 2018 was the year with the most production of kurau nets, with a total catch of kurau nets totaling 7205 kg/year, and the highest catch occurred in March, namely 867.7 kg while the lowest catch occurred in July, namely 166.6 kg. Based on the results of the calculation of the fishing season index, it is known that the fish catch is abundant from January to March. In these months, fishing is excellent, and the peak season is in February. From April to September, the fish catch is minimal, and this month is the wrong time to catch fish.